Comment on "Magnetosensitive neurons mediate geomagnetic orientation in Caenorhabditis elegans" - Lukas Landler; Simon Nimpf; Tobias Hochstoeger; Gregory C Nordmann; Artemis Papadaki-Anastasopoulou; David A Keays (eLife, 2018)
A diverse array of species on the planet employ the Earth's magnetic field as a navigational aid. As the majority of these animals are migratory, their utility to interrogate the molecular and cellular basis of the magnetic sense is limited. Vidal-Gadea and colleagues recently argued that the worm Caenorhabditis elegans possesses a magnetic sense that guides their vertical movement in soil. In making this claim, they relied on three different behavioral assays that involved magnetic stimuli. Here, we set out to replicate their results employing blinded protocols and double wrapped coils that control for heat generation. We find no evidence supporting the existence of a magnetic sense in C. elegans. We further show that the Vidal-Gadea hypothesis is problematic as the adoption of a correction angle and a fixed trajectory relative to the Earth's magnetic inclination does not necessarily result in vertical movement.